Atorvastatin as a potential anti-malarial drug: in vitro synergy in combinational therapy with quinine against Plasmodium falciparum - Pradines Bruno; Rogier Christophe; Amalvict Rémy; Baret Eric; Gil Marine; Briolant Sébastien; Dormoi Jerome; Wurtz Nathalie; Henry Maud; Parquet Véronique (Malaria Journal, 2010)
Abstract Background Quinine (QN) remains the first line anti-malarial drug for the treatment of complicated malaria in Europe and Africa. The emergence of QN resistance has been documented. QN resistance is not yet a significant problem, but there is an urgent need to discover partners for use in combination with QN. The aim of the study was to assess the in vitro potentiating effects of atorvastatin (AVA), a 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor, in combination with QN against Plasmodium falciparum and to evaluate whether the effects of AVA could be associated with gene copy number or mutations in genes involved in QN resistance, such as pfcrt, pfmdr1, pfmrp and pfnhe. Methods The susceptibilities to combination of AVA with QN were assessed against 21 parasite strains using the in vitro isotopic microtest. Genotypes and gene copy number were assessed for pfcrt, pfmdr1, pfmdr2, pfmrp genes. In addition, the number of DNNND, DDNHNDNHNN repeats in pfnhe-1 ms4760 and the ms4760 profile were determined for each strains of P. falciparum. Results AVA demonstrated synergistic effects in combination with QN against 21 P. falciparum strains. The QN IC50 was reduced by 5% (0% to 15%; 95%CI: 1%-8%), 10% (3% to 23%; 95%CI: 7%-14%) and 22% (14% to 40%; 95%CI: 19%-25%) in presence of AVA at concentrations of 0.1, 0.5 and 1.0 μM, respectively. These reductions were all significant (p < 0.009). The reduction in the QN IC50 in presence of AVA was not significantly correlated with the QN IC50 (r = 0.22, P = 0.3288) or the AVA IC50 (r = 0.03, P = 0.8946). The synergistic effect of AVA in combination with QN was not significantly associated with polymorphisms in the pfcrt, pfmdr1, pfmrp, and pfnhe-1 genes that could be involved in QN resistance. The synergistic effect of AVA on QN responses was not significantly associated with pfmdr1 copy number (P = 0.0428). Conclusion The synergistic effect of AVA in combination with QN was found to be unrelated to mutations occurring in transport protein genes involved in QN drug resistance. The different mechanisms of drug uptake and/or mode of action for AVA compared to the other anti-malarial drugs, as well as the AVA-mediated synergy of the anti-malarial effect of QN, suggests that AVA will be a good candidate for combinatorial malaria treatment. All of these observations support calls for both an in vivo evaluation with pharmacokinetic component and clinical trials of AVA as an anti-malarial therapy.